Ask a New Question
Search
Convert the recursive form a1=5,
Convert the recursive from a↓1 = 3, a↓n = -2a↓n-1 to the explicit form.
a. a↓n = 3(-2)^n-1 b. a↓n = -2(3)^n+1 c. a↓n
1 answer
39 views
Convert the recursive form a1=7, an = 3an-1 to explicit form
1 answer
60 views
Convert the recursive form: a1 = 5, an = 2an-1, to the explicit form
1 answer
7 views
Convert the recursive form a^1=7, a^n=3a^n-1 to the explicit form.
a^n=3(7)^n-1 a^n=7(3)^n+1 a^n=7(3)^n-1 a^n=3(7)^n
1 answer
34 views
Convert the recursive form a↓1 = 5, a↓n = 2a↓n-1 to the explicit form.
a. a↓n = 3(7)^n b. a↓n = 5(2)*n-1 c. a↓n =
1 answer
53 views
Convert the recursive form a⬇1=7, an = 3a⬇n-1 to explicit form.
a. a⬇n = 7(3)^n-1 b. a⬇n = 3(7)^n-1 c. a⬇n = 7(3)^n+1
5 answers
44 views
Convert the recursive form a1=5,an=2an-1 to the explicit form.
1 answer
98 views
Convert the recursive form a1=7, an=3an-1 to the explict form
1. an=7(3)^n1 2. an=7(3)^n+1 3. an=3(7)^n 4.an=3(7)^n-1
1 answer
77 views
Convert the recursive form a1 = 5, = 2an-1 to the explicit form
1 answer
48 views
Convert the recursive form a1=5, an=2an−1a1=5, an=2an−1 to the explicit form. (1 point) Responses an=3(7)nan=3(7)nA sub n is
1 answer
6 views